MODEL OF FORMING OF ORATORICAL TRADE AT FUTURE MASTER’S DEGREES OF SOCIAL PEDAGOGIC - Kononenko, Liliya V. (Educological discourse, 2014)
The article highlights the results of the research of problems of forming of oratorical trade at the future master’s degrees of social pedagogic; specificity of oratorical skill in professional and educational activities of the Master's degree of this specialty is determined; the pedagogical basis of solution of this problem is defined and characterized; the expediency of the author's model’s application of forming of oratorical trade at the future master’s degrees of social pedagogic is founded; the content of the components of the proposed model is exposed.